Open innovation in the public sector - Villodre, Julián (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
Open innovation in the public sector is a broad concept which usually refers to the use of internal and external knowledge with the aim of transforming organizations and generating public value. This paper focuses on studying the application of the open innovation concept to the public sector. For this purpose, the paper explores the origins and evolution of the concept, and its relationship with the Smart Governance paradigm. In addition, this paper presents digital innovation communities and living labs as practical applications of the concept.